MALE STUDENTS’ READING COMPREHENSION DIFFICULTIES - Destri Wahyuningsih; Ahmad Ridho Muis (STAI Hubbulwathan Duri, 2020)
The purpose of this research is to find out the factors that influence male students' reading comprehension difficulties on Procedure text at X Class of Madrasah Aliyah Khairul Ummah Islamic Boarding School Batu Gajah. The researcher used Descriptive Analysis Research. In this research, researcher wants to describe the factors that influence male students' reading comprehension difficulties on procedure text at X class of Madrasah Aliyah Khairul Ummah Islamic Boarding School Batu Gajah. This research used the formulation total percentage of the result Internal factors and External factors. Internal factors that are Intelligence got 71%, readiness got 48% and interest 75%. The most internal factor that influence male students’ reading comprehension difficulties on procedure text at the first grade is interest. The external factors that are Family got 20%, school got 26%, and society got 35%. The most eksternal factor that influence male students’ reading comprehension difficulties on procedure text is society.